(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The essence of business process management theory is investigated. It is noted that the effective functioning of the organization in modern conditions is largely determined by the formalization of interacting business processes performed in the organization. The analysis of the business process classification, existing business process models, the estimation of economic efficiency and the analysis of existing systems of business process monitoring are presented. The features of economic-mathematical models of business process reengineering are noted, as well as an example of optimization of the business process of supporting the users of the united territorial community.